Global investigation of olivine on Mars: Insights into crust and mantle compositions. Issue 2 (20th February 2013) - Ody, A.; Poulet, F.; Bibring, J.‐P.; Loizeau, D.; Carter, J.; Gondet, B.; Langevin, Y.
Abstract: [1] We present the distribution of olivine on Mars, derived from spectral parameters based on the 1 µm olivine absorption band. The olivine can be defined with respect to two spectral end‐members: type 1 corresponds to olivine with low iron content and/or small grain size and/or small abundance, and type 2, which corresponds to olivine with higher iron content and/or larger grain size and/or larger abundance. The spatial and statistical analysis of the global olivine distribution points out five major geological settings where olivine is detected: (1) Early Hesperian olivine‐bearing smooth crater floors and flat intercrater plains throughout the southern highlands; (2) olivine deposits around the three main basins Argyre, Hellas, and Isidis; (3) olivine in intercrater dunes, crater ejecta, or extended deposits in the northern plains; (4) olivine associated with outcrops and sand in the floor of Valles Marineris; and (5) olivine‐bearing butte outcrops in the vicinity of Hellas. The geological context, the age, and the composition of the olivine detections associated with these five major geological settings are detailed. Their origin and the implication of their occurrence on the composition of the Martian mantle and crust, as well as on the evolution of Mars volcanism are discussed. Key Points: Global mapping and analysis of olivine bearing deposits Identification of five major geological settings Implications on volcanic and internal evolution of Mars